Template Syntheses and Characterization of 14-Membered Tetraazamacrocyclic Complexes - S. M. Nasman, Omar (Asian Journal of Chemistry, 2010)
A new series of 14-membered tetraazamacrocyclic complexes [CuL]X2, [X = Cl or NO3] and [MLX2] [M = Co2+, Ni2+ and Zn2+, X = Cl or NO3] have been synthesized by template condensation of o-bromoaniline, phthalaldehyde and diaminoethane in ethanol and were characterized by elemental analysis, IR, 1H NMR, electronic spectral, conductivity as well as magnetic susceptibility measurements. An octahedral geometry is proposed for all the complexes except for copper complexes which were found to be square-planar.